농림투융자사업의 투명화와 농업금융의 안정화 과제 - 박성재 (한국농촌경제연구원, 2006)
This study is aimed to review the capital inflow into the agriculture and rural sector with respect to the government and the rural financial market. To progress the structural adjustment of agriculture in the post DDA/WTO era, Korea launched new integrated agricultural and rural development program in 2004. This study focuses on interpreting the program and analyzing its characteristics compared with the past structural adjustment programs since 1992. It is also designed to review the rural financial market situation and suggest new financial services and policy directions. The integrated development program is supported by 119 trillion won investment plan for the period of 2004 to 2013. It changed policy direction from investments to production and from marketing to income support for farm households suffering from stagnant income and increasing debt burden since the mid-1990s. In addition, the portion of investment to rural community development increased to enhance the quality of living of rural residents. However, many farmers did not expect success of the program based on the past experience of investment policy failures and uncertainty of future agricultural environment as protection level of agriculture is lowered. This low level of trust on policy is another barrier for the government to overcome. The information asymmetry of agricultural investment programs is one of the factors which have caused the low level of trust on policy. The government used the total amount of agricultural investments as a way of persuading farmers to accept the market opening policies since the agricultural trade negotiations under Uruguay Round were launched. But this strategy caused farmers to have high expectations for government supports and made taxpayers to regard too much resources allocated to the inefficient sector such as agriculture. In fact, great portion of investments was allocated to modernizing agricultural infrastructure and increasing the farming scale of large farms. This improved productivity and increased supply of agricultural products, which in turn lowered price level and farm income, and increased farm household debts. Many farmers suffering from low income and high debt burden criticize the government and its policy failure. Cooperative credit is a main source of external capital for farmers and the credit guarantee system for farmers is an important policy instrument to reduce failure of rural financial markets. Although the cooperative banking is relatively sound because of strong supports of the credit guarantee fund for farmers, it is expected that this good situation will not be continued as market competition intensifies. Thus, the strong structural adjustment of agricultural cooperatives is needed for the new phase of rural and agricultural environments of market opening. Furthermore, cooperatives should make further efforts to develop new financial services for aging rural community. Researcher: Seong-Jae Park, Yong-Taek Kim, Eui-Sik Hwang,Han-Pil Moon, and Yong-Won Cho E-mail Address: seongjae@krei.re.kr, yongkim@krei.re.kr, eshwang@krei.re.kr, hanpil@krei.re.kr, cyw00@krei.re.kr